(untitled) (Research, Society and Development, 2022)
Corn cob flour is basically made up of hemicellulose, cellulose, lignin, proteins, simple sugars, lipids, starch and water. Its low cost favors the production of affordable food, providing the population with access to these at attractive and competitive costs, combined with essential and functional high nutritional value. In this sense, the present study aimed to produce and characterize a corn cob flour as an alternative of applicability in the preparation or enrichment of food products. Analyzes were performed to determine the functional properties and proximate composition. The average values obtained were: 0.49% (phytic acid), 0.03% (oxalic acid), 2.36% (water holding capacity), 72.82% (carbohydrates), 1.82% (ash ), 8.91% (fibers), 5.0% (water absorption index), 1.32% (lipids), 6.37% (hydrogenonic potential), 2.37% (proteins) and 4.36 % (moisture). The physicochemical results of corn cob flour show low value for moisture, high fiber and ash values ​​when compared with conventional flours such as wheat, corn and cassava, in this perspective this flour may have potential safety in human consumption. As for the corn cob flour production process, the microbiological results met the current legislation, demonstrating suitability for consumption. The corn cob flour produced and analyzed has a great prism to be incorporated or used to enrich foods, as it contributes to a physiological benefit due to its fiber content and low levels of Oxalic and Phytic Acids, in addition to minimizing and mitigating the impacts of inappropriate disposal if it is disposed of in the environment without proper management.